2018
DOI: 10.1126/sciadv.aap8957
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke delivery of MANF promotes functional recovery in rats

Abstract: Delayed delivery of MANF to rat brain after ischemic stroke promotes functional recovery and recruits phagocytic immune cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 30 publications
1
86
0
Order By: Relevance
“…. Other studies also demonstrate expression of MANF by myeloid cells (Neves et al, 2016;Mätlik et al, 2018). It is possible that MANF is expressed by microglia in our Manf fl/fl ::Nestin Cre/1 mice.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…. Other studies also demonstrate expression of MANF by myeloid cells (Neves et al, 2016;Mätlik et al, 2018). It is possible that MANF is expressed by microglia in our Manf fl/fl ::Nestin Cre/1 mice.…”
mentioning
confidence: 52%
“…We have shown that exogenously administered MANF before cerebral ischemia protects cortical neurons in rats (Airavaara et al, 2009) and poststroke delivery of MANF induces functional recovery of rats after cerebral ischemia (Mätlik et al, 2018). Moreover, the infarction size in the MANF-deficient brain is larger, indicating that endogenous MANF has a protective effect on cortical neurons against ischemic injury (Mätlik et al, 2018). Therefore, we examined ER stress in the Manf -/primary cortical neurons.…”
mentioning
confidence: 99%
“…Cellular count for MANF/BrdU positive cells is presented in Figure 6C. The number of MANF/BrdU + cells was increased in DHA-treated rats compared to saline-treated rats in peri-infarct cortex and DG on Day 14. ing ischemic stroke increased the quantity of phagocytic microglia at 4 days in the peri-infarct region, 31,32 and rhMANF promoted neuron proliferation and prevented neuronal apoptosis. 33 Our study found that MANF was upregulated in neurons and The microglia cell surface receptor TREM2 is highly expressed in response to neuronal cell damage, and its decreased abundance inhibits prolonged phagocytic microglial activity following injury.…”
Section: Dha Improves Long-term Survival Attenuates Infarct Sizementioning
confidence: 89%
“…Indeed, when applied to the animals with severe chemically induced Parkinsonian symptoms, these factors significantly improve the neurological scores and reduce histological brain damages ( Lindholm et al, 2007 ; Airavaara et al, 2009 ; Voutilainen et al, 2009 , 2011 ; Huotarinen et al, 2018 ). MANF is also neurorestorative in the rat model of cerebral stroke ( Matlik et al, 2018 ). The cytoprotective mechanisms of MANF and CDNF are currently poorly understood.…”
Section: Introductionmentioning
confidence: 99%